The selection index of S3 corn convergent breeding population based on multivariate analysis - MAKMUR MAKMUR; MUH. FARID; AMBO ALA; KATRIANI MANDJA; MUHAMMAD FUAD ANSHORI; ANNASTYA NUR FADHILAH (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Makmur, Farid M, Ala A, Mandja K, Anshori MF, Fadhilah AN. 2024. The selection index of S3 corn convergent breeding population based on multivariate analysis. Biodiversitas 25: 1097-1103. Corn is one of the most important and strategic food crops in the world, including Indonesia. Increasing corn production through a plant breeding program by assembling hybrid varieties begins with developing a convergent breeding population and index selection. The research aims to identify genetic variance and the effectiveness of selection indices in selecting high-yield S3 cross populations. The research was carried out in Rea Village, Binuang Sub-District, Polewali Mandar District, West Sulawesi from July to November 2022. The research used an augmented design with four blocks. Sixty-six lines were derived from 4 double cross populations and 8 populations of the S3 generation multiple-cross population, as well as 9 check varieties (NK7328, Pioneer 36, Bisi 18, Bisi 2, NK99, Nasa 29, JH45, Bisi 9, and NK212) were used in this study. The results indicate that the length of cobs (5.98;73.59%), length of seed cobs (7.06; 79.46%), weight of 100 seeds (7.75; 89.30%), and weight of seeds per cob (7.84; 65.59%) have moderate genetic variance and high heritability. The characteristics of stem diameter, yield percentage, and weight of seed per cob were effectively used in the selection index formulation. Based on the index selection, there were 14 potential corn lines with a good performance, recommended for the next hybridization stage.